The effect of operational efficiency on some financial indicators according to the CAMEL model of banking financial stability: An applied research on a sample of Iraqi private banks for the period 2010-2020 (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Abstract          The research aims to determine the nature of the Iraqi market in terms of banking financial stability and the extent impact of the operational efficiency on it, Accordingly, chosen 15 relational banks were chosen as an intentional sample that could represent the Iraqi banking system for the period 2010-2020. The operational efficiency variable was measured according to the data envelope model, and banking financial stability used  CAMELS model which includes five indicators (capital adequacy, asset quality, management quality, profitability, and liquidity), so for testing the research hypotheses used the random regression model by adopting the STATA software,  results of the hypothesis test was  found direct effect of operational efficiency in the banking financial stability indicators.